Legal Dynamics of the Use of Presidential Threshold in the Indonesian Presidential System - Koedoeboen, Arman (UNISSULA, 2025)
This research examines the legal framework of the Presidential Threshold (PT) as stipulated in Law Number 7 of 2017 concerning General Elections, analyzing its effects on political stability, democratic representation, and the inclusiveness of the political process. Using a qualitative approach through literature study, the research reveals that while the PT mechanism, which requires a party or coalition to hold at least 20% of parliamentary seats or 25% of the national vote, contributes to reducing electoral fragmentation and promoting political stability, it also limits the diversity of candidates and political ideologies, potentially undermining democratic principles. The study highlights how this statutory provision restricts the participation of smaller political parties and independent candidates, consolidating power within larger political coalitions. It also raises constitutional concerns regarding the right to political participation under the 1945 Constitution and the fairness of the electoral system. The findings suggest that reforms to the legal basis of the PT, such as lowering the threshold or exploring alternative electoral systems, could enhance the inclusivity and representativeness of Indonesia’s presidential election process. Future research should focus on assessing the long-term effects of the PT's legal design on voter engagement and political trust in Indonesia.